Effectiveness of Dextrose Prolotherapy in Chronic Plantar Fasciitis: A Cross-Sectional Study - Mahato, Ajay; Gupta, Mithlesh Kumar; Panthee, Rajan; Pathak, Manish Raj; Nepal, Santosh (Birat Journal of Health Sciences, 2023)
Introduction: Plantar fasciitis is a very common musculoskeletal condition encountered in the outpatient department of orthopedics. It’s the most common cause of heel pain. Patients have pain on weight-bearing, which limits their activities. Usually, plantar fasciitis is diagnosed on the basis of history and clinical examination; however, X-ray and USG can be helpful in atypical presentations. Mostly, plantar fasciitis is managed conservatively, which includes stretching exercises, footwear modification, ultrasonics, and injections. Prolotherapy is a very cost-effective, and OPD-based procedure that has shown promising results in many tendinopathies. There are no other risks involved in this procedure, and patients can start light activities immediately after the injection. Objective: To evaluate the efficacy of dextrose prolotherapy in the treatment of chronic resistant plantar fasciitis (PF). Methodology: This prospective, cross-sectional study, was conducted from July 2021 to December 2021 at Birat Medical College and Teaching Hospital after taking permission from the Institutional Review Committee (IRC). Patient selection was done using inclusion and exclusion criteria. A total of 66 patients were included in the study, who received two prolotherapy injections in a gap of two weeks and were followed up after 12 weeks. Patient’s clinical (Visual Analogue Score for pain at rest and activities), functional (Foot Function Index), and ultrasonograhic (plantar fascia thickness) findings were noted pre- and post-test and were evaluated. Results: There were 66 adult patients included in the study, out of which 39 patients (59.1%) were female and 27 patients (40.1%) were male. Their age ranged from 26 to 68 years, with a mean age of 43.91 and a standard deviation (SD) of 10.225. The mean BMI was 25.758 with an SD 2.69 (range: 19.6-33.2). The clinical score (VAS-R and VAS-A), functional score (FFI), and ultrasonographic findings (PF thickness) yielded significant outcomes following prolotherapy. Conclusion: Prolotherapy is a safe, economical, and effective treatment module for plantar fasciitis that has shown significant improvement in pain, functional outcomes, and patient satisfaction.